Map of the Colony of Victoria, shewing the counties, settled districts, electoral districts and boroughs, townships, gold fields, coal fields, tin mines, railways, roads, rivers, etc. etc. etc. - Century Map Productions ([Melbourne] : Century Map Productions, 1979)
Shows public buildings and maps of Geelong and Melbourne suburbs excircling main map with floral designs.
Presented by the proprietors of "The Age" to their subscribers, Melbourne, Victoria, October 17th 1854.
Copy of an original in the Map Collection, State Library of Victoria, by permission of the Library Council of Victoria.
Keywords: Victoria -- Maps